Human Rights In The Age Of Artificial Intelligence: Opportunities and Challenges - Javier Ramirez; Rachel Chen; James Wu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article examines the impact of artificial intelligence (AI) on human rights, focusing on issues such as discrimination, transparency, and accountability. The research analyzes AI applications in areas like law enforcement, employment, and social media, evaluating how AI can both enhance and threaten human rights. The study calls for the development of AI regulations that uphold human rights principles and prevent misuse.